2020
DOI: 10.22271/chemi.2020.v8.i2w.8975
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and extent of contribution of profile characteristics of turmeric growers towards their knowledge about improved cultivation practices in Belagavi, Karnataka

Abstract: The study was conducted in Belagavi district of Karnataka. A total of 120 respondents were selected randomly which includes 60 respondents from Gokak and Raibag taluks where production, productivity and area under turmeric was found maximum. The data collected from the respondents using structured interview schedule and was analyzed and tabulated using statistical tools like correlation and multiple regression analysis. The findings of the study revealed that, the variables landholding, annual income, risk ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…This indicates that the cumin growers had taken reasonable effort to stand with difficult and uncertain situations effectively. This finding is in line with finding of Chigadolli et al (2020), Gohil (2010), Jadeja et al (2017), Kumar et al (2014), More et al (2015), Tavethiya et al (2021)…”
Section: Results and Discussion (A) Adoption Of The Crisis Management...supporting
confidence: 92%
“…This indicates that the cumin growers had taken reasonable effort to stand with difficult and uncertain situations effectively. This finding is in line with finding of Chigadolli et al (2020), Gohil (2010), Jadeja et al (2017), Kumar et al (2014), More et al (2015), Tavethiya et al (2021)…”
Section: Results and Discussion (A) Adoption Of The Crisis Management...supporting
confidence: 92%
“…In general, in all the years tuber yield of FLDs plots was higher as compared to check which may be due to good variety, rhizome (Seed) treatment, recommended fertilizer doses, plant protection measures followed by the demonstrators and scientists in the demonstrations plots. The similar results were also observed by Kumar et al, (2012); Dayanan et al, (2013); Meena and Singh (2013); Lal (2014), Sharma and Choudhary (2014); Sahoo et al, (2015); Karthik and Amarnath (2014); Babu and Tirpathi (2015); Babu et al, (2015); Mishra and Singh (2017); Kant et al, (2020); and Chigadolli, et al, (2020). Hence, it can be concluded that increased yield was due to adoption of improved variety and demonstrations of proven technologies.…”
Section: Yield Performancesupporting
confidence: 70%